Evolução da acidentalidade da malha rodoviária da região central do Estado de São Paulo - Massaro, Camila Mota (Universidade Federal de São Carlos, 2018)
Given the current economic situation in Brazil, an efficient financial management, is more easily achieved if they are identified as priorities of future investments. In this context, the classification of the regional road network according to accidentality is fundamental in the definition of intervention priorities. Thus, this paper, in general, proposes to perform an analysis of the evolution of the accidentality of the road network of the central region of the state of São Paulo (DR-4 DER-SP), between the periods of 2010 to 2014. From the object of study, the data on road accidents were collected; These data were analyzed and treated in order to produce the road network in GIS platform. Then, the appropriate methodologies were defined to obtain the blackspots of the DR-4 road network. With the results obtained, the blackspots of the central road network of the State of São Paulo were identified through two methods, the accident rate and the severity rate, to compare the methods used. Thus, with the identification of these blackspots and with the series of the evolution of accidentality, it is possible to intervene on the highways to reduce the number of accidents in the region.
Keywords: Acidente de tráfego; Pontos críticos; Malha rodoviária; Rodovias estaduais; Traffic accident; Black spot; Road network; State Highways; ENGENHARIAS::ENGENHARIA CIVIL::INFRA-ESTRUTURA DE TRANSPORTES